2014
DOI: 10.1155/2014/145943
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Imaging of Auditory and Auditory-Limbic Connectivity in Tinnitus: Preliminary Evidence and Methodological Challenges

Abstract: Subjective tinnitus, or “ringing in the ears,” is perceived by 10 to 15 percent of the adult population and causes significant suffering in a subset of patients. While it was originally thought of as a purely auditory phenomenon, there is increasing evidence that the limbic system influences whether and how tinnitus is perceived, far beyond merely determining the patient's emotional reaction to the phantom sound. Based on functional imaging and electrophysiological data, recent articles frame tinnitus as a “ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 65 publications
7
52
0
6
Order By: Relevance
“…The partial correlation coefficient between FA, MD and radial diffusivity values and BDI is −0.6279, 0.6092 and 0.6177, respectively (p<0.05, adjusted for age and gender) studies have reported that increased axial diffusivity was associated with chronic pain or hyperalgeria [18,19]. This voxel-based regional change in the present study is the confirmatory finding that supports a previous ROI study that also showed a difference in DTI values in the auditory cortices of tinnitus patients compared with normal control subjects [6]. The dominant change in DTI values on the left side is consistent with prior studies demonstrating significant change in left cerebral WM [6,9].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The partial correlation coefficient between FA, MD and radial diffusivity values and BDI is −0.6279, 0.6092 and 0.6177, respectively (p<0.05, adjusted for age and gender) studies have reported that increased axial diffusivity was associated with chronic pain or hyperalgeria [18,19]. This voxel-based regional change in the present study is the confirmatory finding that supports a previous ROI study that also showed a difference in DTI values in the auditory cortices of tinnitus patients compared with normal control subjects [6]. The dominant change in DTI values on the left side is consistent with prior studies demonstrating significant change in left cerebral WM [6,9].…”
Section: Discussionsupporting
confidence: 91%
“…Other research that compared tinnitus and control with hearing loss by using a region-of-interest (ROI) method also showed that FA was negatively correlated with hearing loss in the left auditory cortex and increased FA at the WM tracts underneath both auditory cortices [6]. These authors hypothesized that decreased FA would be related to hearing loss and increased FA, indicating increased tract density would be a compensation of hearing loss [6]. In spite of these previous research achievements, the relationship between WM integrity and symptom grade or clinical variables in tinnitus remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations